Comparison of properties of tablets and energy profile of compaction of two spray-dried lactoses - Muzíková, Jitka; Sináglová, Pavla (Acta poloniae pharmaceutica, 2013)
The paper compared two spray-dried lactoses Flowlac 100 and SuperTab 14SD from the standpoint of tensile strength and disintegration time of tablets, the effect of an addition of the lubricant magnesium stearate and silicified microcrystalline cellulose on these properties, and also from the standpoint of the energy profile of compression. The comparison of the values was performed at the compression force of 15 kN. The strength of tablets was higher in the case of SuperTab 14SD, an increase in the concentration of magnesium stearate did not decrease tablet strength. Prosolv SMCC 90 increased the strength of tablets and made it equal for both lactoses, but it also increased the sensitivity to the added lubricant. The disintegration time of tablets was shorter in the case of SuperTab 14SD, an increased concentration of magnesium stearate prolonged it, and an addition of Prosolv SMCC 90 shortened it and made it equal for both lactoses. From the energy standpoint, the maximal energy was higher in the case of SuperTab 14SD, an addition of Prosolv SMCC 90 increased it and again made it equal for both lactoses. The differences in the values of the maximal energy were primarily due to the values of the energy for friction and the energy accumulated by the tablet after compression, and there was no marked difference in the values of the energy of decompression. SuperTab 14SD showed a higher plasticity than Flowlac 100.
Keywords: pevnost v tlaku; farmaceutická chemie; Tensile Strength; Stearic Acids; Lactose; aerosoly; pomocné látky; celulosa; rozpustnost; Excipients; Aerosols; Compressive Strength; laktosa; Kinetics; vysoušení; tablety; Cellulose; Lubricants; Technology, Pharmaceutical; Solubility; kyseliny stearové; pevnost v tahu; Chemistry, Pharmaceutical; farmaceutická technologie; lubrikanty; Desiccation; kinetika; Tablets